SOSIALISASI IMPLEMENTASI KURIKULUM MERDEKA BELAJAR PADA GURU TINGKAT SD/MI DI DESA JANTI KECAMATAN MOJOAGUNG JOMBANG - Sirojudin, Didin Sirojudin; Lilawati, Emi; Waslah, Waslah; Agustin, Wiranda Dwi; Hamidah, Salsabilla; Sari, Ayu Novia; Saputra, Sharul (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
The Seminar on the Implementation of the Merdeka Curriculum at MI Al-Mu’awwanah is an important event aimed at discussing and promoting the implementation of the Merdeka Curriculum in the Madrasah Ibtidaiyah (MI) Al-Mu’awwanah. The Merdeka Curriculum represents an educational innovation that allows MI to be more adaptive and responsive to current educational developments. This seminar will address key aspects of the Merdeka Curriculum, including student-centered learning methodologies, competency development, and assessments that focus on deep understanding. Additionally, the seminar will also discuss the challenges and opportunities in implementing the Merdeka Curriculum at MI Al-Mu’awwanah. It is expected that this seminar will provide valuable insights for educators, teaching staff, and relevant stakeholders in their efforts to enhance the quality of education at MI Al-Mu’awwanah through the innovative and relevant implementation of the Merdeka Curriculum. Keywords: Seminar, Implementation, Merdeka Curriculum, MI Al-Mu’awwanah.